ANALISIS MAKRO EKONOMI DAN INDEKS DOW JONES TERHADAP VOLATILITAS PASAR SAHAM INDONESIA - Noviarti (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2018)
This study aims to determine how macroeconomic factors and the Dow Jones Index affect the volatility of the Indonesian stock market. Volatility The Indonesian stock market is represented by Indonesia Composite Index, and macroeconomic factors are represented by variables of Inflation, Exchange Rate, BI Rate, Gold Price and American Capital Market Performance represented by the Dow Jones Index. Observation period from January 1, 2018 to January 15, 2018 with daily data. From the results of the test data obtained results that the Exchange Rate and Dow Jones Index significantly affect the volatility of Indonesian stock market prices during the observation period. Inflation variables, BI rates and gold prices have no significant effect.